A wear-resistant electroplating protective coating and a method of using the same
Through wear-resistant electroplating protective coatings and screen printing technology, combined with UV curing and baking treatment, the problems of inconsistent quality and low efficiency of traditional electroplating protection methods are solved, and the uniformity and efficient protection of the electroplating layer are achieved. In batch production and diversified products.
Patent Information
- Application Number
- CN202411510668.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Traditional anti-electroplating protection methods have problems such as inconsistent quality, low efficiency, waste of materials and inconsistent electroplating layers, especially in mass production and processing of different patterns and shapes.
Using wear-resistant electroplating protective coatings, combined with wire mesh by modifying polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexylphenyl ketone, modified nanohydrated silica and silicone defoaming agent. Printing technology and UV curing technology form a wear-resistant, scratch-resistant and water-resistant coating, and are easily peeled off by baking.
It realizes effective protection of the substrate during the electroplating process, ensures the uniformity and quality of the electroplating layer, improves production efficiency, reduces material use and site requirements, and is suitable for mass production and products with different patterns and shapes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electroplating protective coatings and relates to a wear-resistant electroplating protective coating and a use method thereof. Background Art
[0002] Traditional local protection against electroplating uses a masking method: some use plastic materials (such as instant stickers, PVC stickers, etc.), cut patterns and stick them on the surface of the substrate for temporary protection, and then tear them off manually after the electroplating is completed. This method requires manual pasting of patterns, which can easily lead to inconsistent quality and requires high application experience of the operator. In addition, this method requires the film material to be cut into the required patterns in advance, which is inefficient and manual pasting of patterns can easily lead to inconsistent quality and requires high application experience of the operator. It also has high requirements for the adhesion of the film to the substrate. If the adhesion is too high, it is not easy to tear off, and if the adhesion is too low, it may fall off during the cleaning process. It can not achieve good protection; some use metal plates, and the cut and formed plates cover the surface of the substrate. During the electroplating process, the parts of the substrate that do not need to be electroplated are protected. After the electroplating is completed, they need to be stored. This method requires a lot of materials and sites for mass production. It can only achieve the reuse of single project products. If different patterns and shapes are encountered, they need to be prepared separately; in the electroplating process, due to the thickness of the plate and the surface of the substrate, there is a gap, which will cause the thickness of the electroplated film on the edge of the protective pattern to increase or decrease, so that the consistency of the electroplating coating is poor, so laser-assisted cleaning is required.
[0003] Therefore, the present invention is developed for this process to ensure that it can withstand water washing and roller brush friction in a cleaning environment, ensure effective anti-plating protection for the substrate during the electroplating stage, and bake after the electroplating is completed to reduce the adhesion of the coating to the substrate, thereby easily peeling off and removing it from the surface of the substrate. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant electroplating protective coating and a use method thereof, which has the characteristics of wear resistance, scratch resistance and water washing resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant electroplating protective coating, the coating is composed of the following components by mass percentage: 50-70% of modified polyurethane acrylate, 20-30% of hydroxyethyl methacrylate, 2-5% of hydroxycyclohexyl phenyl ketone, 2-5% of trimethylbenzoyl diphenoxyphosphine, 4-5% of modified nano hydrated silicon dioxide, 1-3% of coloring auxiliary agent, and 1-3% of organic silicon defoaming agent.
[0007] Wherein, the preparation method of modified polyurethane acrylate is as follows:
[0008] Dissolving a silane coupling agent in deionized water to prepare a silane coupling agent solution with a mass fraction of 50-60%, adding polyurethane acrylate to the silane coupling agent solution, wherein the mass ratio of polyurethane acrylate to silane coupling agent is 1:1, stirring at a speed of 150 r / min, heating to 50° C. while stirring, stirring for 1 hour, then adding 5-10wt% of vermiculite powder, heating to 65° C., and continuing to stir at a speed of 200 r / min for 1 hour to obtain the modified polyurethane acrylate;
[0009] The preparation method of modified nano hydrated silica is as follows:
[0010] S1.1: dissolving graphene oxide in deionized water and ultrasonicating for 1 h to obtain a graphene oxide solution with a mass fraction of 50%;
[0011] S1.2: Mix hydrated silicon dioxide and aluminum oxide in a mass ratio of 2:1, put them into a ball mill, and grind them at a speed of 400 r / min for 1 h to obtain a mixture A with a particle size of 150 mesh;
[0012] S1.3: Dispersing mixture A in the graphene oxide solution, wherein the mass ratio of mixture A to graphene oxide is 1:1, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture B;
[0013] S1.4: freeze the solid-liquid mixture B in liquid nitrogen for 15-20 min. After freezing, dry it at -70--50°C in a vacuum state for 4-6 h to obtain a mixture C.
[0014] S1.5: After adding 2 wt% of rare earth oxide and 1 wt% of dispersant to mixture C, the mixture was ground in a ball mill at a speed of 500 r / min for 1 h to obtain mixture D;
[0015] S1.6: The mixture D is heated from room temperature to 400°C for calcination for 3 hours, and the calcined solid is crushed and ground to a particle size of 200 mesh to obtain the modified nano hydrated silica;
[0016] The coating preparation method is as follows:
[0017] Modified polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexyl phenyl ketone, trimethylbenzoyl diphenoxyphosphine, modified nano hydrated silica, coloring aid, and silicone defoamer are placed in a blender in proportion and stirred at a stirring rate of 200-300 r / min for 8 hours to obtain the coating.
[0018] Furthermore, the coloring auxiliary agent is polyoxyethylene oleate A-110.
[0019] Furthermore, the organosilicon defoamer is one of BYK-141, BYK-077, and BYK-066N.
[0020] Furthermore, the silane coupling agent is one of silane coupling agent KH-560 and silane coupling agent KH-792.
[0021] Furthermore, the rare earth oxide in S1.5 is one of cerium oxide, lanthanum oxide and praseodymium oxide.
[0022] Furthermore, the dispersant in S1.5 is polyethylene glycol, and the number average molecular weight is 2000-4000.
[0023] Furthermore, the heating rate from room temperature to 400° C. in S1.6 is 5° C. / min.
[0024] A method for using a wear-resistant electroplating protective coating, the coating is used as follows:
[0025] S2.1: First, wash the surface of the substrate with deionized water, and then purge it with nitrogen at 70°C for 2-3 hours at a nitrogen flow rate of 20 m / s to obtain a substrate with a dry surface;
[0026] S2.2: The coating is applied to the substrate surface using screen printing technology, and then UV-cured coating is used, with a coating thickness of 20~30μm;
[0027] S2.3: The substrate surface after the coating is cured is cleaned again, and dried at 80°C for 4 hours after cleaning. The dried substrate surface is electroplated. After the electroplating is completed, the substrate surface is baked. After the baking treatment, the coating is peeled off to protect the coating-coated part of the substrate surface during the electroplating process.
[0028] Furthermore, the parameters of the UV curing coating in S2.2 are ultraviolet wavelength of 355-365 nm and curing time of 5-10 s.
[0029] Furthermore, the parameters of the baking treatment in S2.3 are a temperature of 90-100° C. and a drying time of 1-2 hours.
[0030] The polyurethane acrylate in the present invention was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. with a purity of 98%; the vermiculite in the present invention was purchased from Shanghai Dibai Biotechnology Co., Ltd. with a product number of K740844; the nano hydrated silica in the present invention was purchased from Chengdu McCahey Chemical Co., Ltd. with a purity of 98%.
[0031] Polyurethane acrylate (PUA) combines the wear resistance of polyurethane with the weather resistance and water resistance of acrylate, providing the coating with excellent physical properties and chemical stability, enabling it to resist external mechanical friction and chemical erosion.
[0032] In order to further improve the wear resistance and cleaning resistance of polyurethane acrylate, the present invention uses silane coupling agent and vermiculite to modify it. The silane coupling agent has different reactive groups at both ends, one end can react with the functional group in PUA, and the other end can form a chemical bond with vermiculite powder. In this way, the silane coupling agent can serve as a bridge to connect PUA and inorganic fillers, improve the compatibility and interfacial bonding between them, and thus improve the water resistance of PUA; vermiculite is a layered silicate mineral with good adsorption, thermal insulation and chemical stability. Adding vermiculite powder to PUA can improve the thermal stability and mechanical properties of the composite material. At the same time, the silane coupling agent acts as a bridge to connect PUA and vermiculite powder, further enhancing the mechanical properties of the composite material.
[0033] In the coating formulation, hydroxyethyl methacrylate as an auxiliary agent and modifier can enhance the adhesion, rheology and water resistance of the coating. By forming hydrogen bonds with the substrate, hydroxyethyl methacrylate helps to improve the bonding between the coating and the substrate and prevent the coating from falling off. At the same time, it can also improve the construction performance of the coating, making the coating more uniform and smooth. Hydroxycyclohexyl phenyl ketone as a photoinitiator plays a key role in the UV curing system. It can absorb UV energy, initiate polymerization reaction in the coating, and make the coating cure quickly. Hydroxycyclohexyl phenyl ketone also has good non-yellowing properties, which can ensure that the cured coating maintains bright color for a long time. Also as a photoinitiator, trimethylbenzoyl diphenoxy phosphine and hydroxycyclohexyl phenyl ketone work together It has a wide absorption range and high curing speed, and is particularly suitable for the curing of colored systems and thick film layers. As a nanofiller, modified nano hydrated silica can significantly improve the hardness, wear resistance and corrosion resistance of the coating. Nano hydrated silica particles have strong toughness and chemical resistance, which can enhance the physical barrier effect of the coating and prevent erosion by external substances. At the same time, it can also improve the adhesion between the coating and the substrate and enhance the overall stability of the coating. The silicone defoamer plays a defoaming role in the preparation and construction of the coating. It can effectively eliminate bubbles and foam in the coating, prevent defects such as pinholes and pits from appearing on the surface of the coating, and improve the overall quality and aesthetics of the coating.
[0034] The addition of modified nano hydrated silica in the present invention can significantly improve the hardness and wear resistance of the coating, making it more resistant to external friction and wear. By forming a better physical and chemical bond with the substrate, the modified nano hydrated silica enhances the adhesion between the coating and the substrate, thereby reducing the risk of the coating falling off. In addition, the nano-scale particle size of the modified nano hydrated silica enables it to be evenly dispersed in the coating to form a strong network structure, thereby improving the overall performance of the coating.
[0035] In the modification process of nano-hydrated silica, graphene oxide is added as a reinforcing phase and dispersant. The modified nano-hydrated silica can significantly improve the mechanical properties and dispersibility of the coating. Its unique two-dimensional structure enables the coating to better disperse stress when subjected to external forces, thereby improving wear resistance. As a filler for the coating, the mixture of nano-hydrated silica and alumina can provide the basic properties and structure required by the coating. The addition of alumina can further enhance the hardness and wear resistance of the coating; rare earth oxides as modifiers can significantly improve the high temperature resistance and oxidation resistance of the coating. At the same time, it can also promote the growth and arrangement of crystals in the coating, thereby improving the hardness and wear resistance of the coating.
[0036] The present invention uses screen printing technology to apply the coating on the surface of the substrate during use, which can achieve precise coating of the coating, avoid waste of the coating and pollution of the substrate, clarify the scope of local protection, and adopt a screen printing method. Only one screen is needed for different patterns and shapes. The screen printing method can ensure the consistency of the film layer of each printed sheet and there is no large gap with the substrate, which will not affect the electroplating effect. The screen printing method can effectively improve production efficiency and reduce and reduce the time cost in the turnover process of the traditional mask method; UV curing technology is adopted, the coating can be quickly cured in a short time, and production efficiency is improved; the coating is stripped and removed by baking treatment, so that the surface of the substrate coated with the coating during the electroplating process can be accurately protected, and pollution and damage of the non-electroplating area can be avoided; the coating prepared by the present invention has excellent wear resistance, can provide effective protection for the substrate during the electroplating process, avoid wear and damage during the electroplating process, and due to the protective effect of the coating, the electroplating layer can be more evenly and densely attached to the surface of the substrate, thereby improving the quality and performance of the electroplating layer.
[0037] Beneficial effects of the present invention:
[0038] The present invention uses silane coupling agent and vermiculite to modify polyurethane acrylate, further improving the wear resistance and cleaning resistance of polyurethane acrylate. The silane coupling agent can serve as a bridge to connect PUA and inorganic filler, improve the compatibility and interface bonding force between them, and thus improve the water resistance of PUA. Vermiculite is a layered silicate mineral with good adsorption, thermal insulation and chemical stability. Adding vermiculite powder to PUA can improve the thermal stability and mechanical properties of the composite material.
[0039] The addition of modified nano hydrated silicon dioxide in the present invention can significantly improve the hardness and wear resistance of the coating, making it more resistant to external friction and wear. By forming a better physical and chemical bond with the substrate, the modified nano hydrated silicon dioxide can enhance the adhesion between the coating and the substrate, thereby reducing the risk of the coating falling off. In addition, the nanometer-scale particle size of the modified nano hydrated silicon dioxide enables it to be evenly dispersed in the coating to form a strong network structure, thereby improving the overall performance of the coating.
[0040] The present invention uses screen printing technology to apply the coating on the surface of the substrate during use, which can achieve accurate coating of the coating, avoid waste of the coating and pollution of the substrate, and clarify the scope of local protection. DETAILED DESCRIPTION
[0041] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0042] Coating formula 1: modified polyurethane acrylate 60%, hydroxyethyl methacrylate 25%, hydroxycyclohexyl phenyl ketone 3%, trimethylbenzoyl diphenoxy phosphine 3%, modified nano hydrated silica 5%, oleic acid polyoxyethylene ester A-110 2%, silicone defoamer BYK-141 2%;
[0043] Coating formula 2: modified polyurethane acrylate 50%, hydroxyethyl methacrylate 30%, hydroxycyclohexyl phenyl ketone 5%, trimethylbenzoyl diphenoxyphosphine 5%, modified nano hydrated silica 5%, oleic acid polyoxyethylene ester A-110 2%, silicone defoamer BYK-077 3%;
[0044] Coating formula 3: modified polyurethane acrylate 70%, hydroxyethyl methacrylate 20%, hydroxycyclohexyl phenyl ketone 2%, trimethylbenzoyl diphenoxy phosphine 2%, modified nano hydrated silica 4%, oleic acid polyoxyethylene ester A-110 1%, silicone defoamer BYK-066N 1%.
[0045] Example 1
[0046] The preparation method of modified polyurethane acrylate is as follows:
[0047] Dissolving silane coupling agent KH-560 in deionized water to prepare a silane coupling agent solution with a mass fraction of 50%, adding polyurethane acrylate to the silane coupling agent solution, wherein the mass ratio of polyurethane acrylate to silane coupling agent is 1:1, stirring at a speed of 150 r / min, heating to 50° C. while stirring, stirring for 1 hour, then adding 7wt% of vermiculite powder, heating to 65° C., and continuing to stir at a speed of 200 r / min for 1 hour to obtain the modified polyurethane acrylate;
[0048] The preparation method of modified nano hydrated silica is as follows:
[0049] S1.1: dissolving graphene oxide in deionized water and ultrasonicating for 1 h to obtain a graphene oxide solution with a mass fraction of 50%;
[0050] S1.2: Mix hydrated silicon dioxide and aluminum oxide in a mass ratio of 2:1, put them into a ball mill, and grind them at a speed of 400 r / min for 1 h to obtain a mixture A with a particle size of 150 mesh;
[0051] S1.3: Dispersing mixture A in the graphene oxide solution, wherein the mass ratio of mixture A to graphene oxide is 1:1, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture B;
[0052] S1.4: The solid-liquid mixture B was placed in liquid nitrogen and frozen for 15 min. After the freezing, it was dried at -70 °C under vacuum for 4 h to obtain a mixture C.
[0053] S1.5: After adding 2 wt % cerium oxide and 1 wt % polyethylene glycol 2000 to mixture C, the mixture was ground in a ball mill at a speed of 500 r / min for 1 h to obtain mixture D;
[0054] S1.6: The mixture D is heated from room temperature to 400°C for calcination at a heating rate of 5°C / min for 3 hours, and the calcined solid is crushed and ground to a particle size of 200 mesh to obtain the modified nano hydrated silica;
[0055] The coating preparation method is as follows:
[0056] According to coating formula 1, modified polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexyl phenyl ketone, trimethylbenzoyl diphenoxyphosphine, modified nano hydrated silica, oleic acid polyoxyethylene ester A-110, and silicone defoamer BYK-141 are placed in a mixer and stirred at a stirring rate of 200 r / min for 8 hours to obtain the coating.
[0057] The coating is used as follows:
[0058] S2.1: First, wash the surface of the substrate with deionized water, and then purge it with nitrogen at 70°C for 2 hours at a nitrogen flow rate of 20 m / s to obtain a substrate with a dry surface;
[0059] S2.2: The coating is applied to the substrate surface using screen printing technology, and then UV curing coating is used, with parameters of UV wavelength of 365 nm, curing time of 7 seconds, and coating thickness of 30 μm;
[0060] S2.3: After the coating is cured, the surface of the substrate is cleaned again, and then dried at 80°C for 4 hours. The dried surface of the substrate is electroplated. After the electroplating is completed, the surface of the substrate is baked. The baking parameters are a temperature of 100°C and a drying time of 1.5 hours. After the baking treatment, the coating is peeled off to protect the surface of the substrate coated with the coating during the electroplating process.
[0061] Example 2
[0062] The preparation method of modified polyurethane acrylate is as follows:
[0063] Dissolving silane coupling agent KH-792 in deionized water to prepare a silane coupling agent solution with a mass fraction of 60%, adding polyurethane acrylate to the silane coupling agent solution, wherein the mass ratio of polyurethane acrylate to silane coupling agent is 1:1, stirring at a speed of 150 r / min, heating to 50° C. while stirring, stirring for 1 hour, then adding 5wt% of vermiculite powder, heating to 65° C., and continuing to stir at a speed of 200 r / min for 1 hour to obtain the modified polyurethane acrylate;
[0064] The preparation method of modified nano hydrated silica is as follows:
[0065] S1.1: dissolving graphene oxide in deionized water and ultrasonicating for 1 h to obtain a graphene oxide solution with a mass fraction of 50%;
[0066] S1.2: Mix hydrated silicon dioxide and aluminum oxide in a mass ratio of 2:1, put them into a ball mill, and grind them at a speed of 400 r / min for 1 h to obtain a mixture A with a particle size of 150 mesh;
[0067] S1.3: Dispersing mixture A in the graphene oxide solution, wherein the mass ratio of mixture A to graphene oxide is 1:1, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture B;
[0068] S1.4: The solid-liquid mixture B was placed in liquid nitrogen and frozen for 20 min. After the freezing, it was dried at -50 °C under vacuum for 6 h to obtain a mixture C.
[0069] S1.5: After adding 2 wt % lanthanum oxide and 1 wt % polyethylene glycol 4000 to mixture C, the mixture was ground in a ball mill at a speed of 500 r / min for 1 h to obtain mixture D;
[0070] S1.6: The mixture D is heated from room temperature to 400°C for calcination at a heating rate of 5°C / min for 3 hours, and the calcined solid is crushed and ground to a particle size of 200 mesh to obtain the modified nano hydrated silica;
[0071] The coating preparation method is as follows:
[0072] According to coating formula 2, modified polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexyl phenyl ketone, trimethylbenzoyl diphenoxyphosphine, modified nano hydrated silica, oleic acid polyoxyethylene ester A-110, and silicone defoamer BYK-077 are placed in a mixer and stirred at a stirring rate of 300 r / min for 8 hours to obtain the coating.
[0073] The coating is used as follows:
[0074] S2.1: First, wash the surface of the substrate with deionized water, and then purge it with nitrogen at 70°C for 3 hours at a nitrogen flow rate of 20 m / s to obtain a substrate with a dry surface;
[0075] S2.2: The coating is applied to the substrate surface by screen printing technology, and then UV curing coating is used, with the parameters of ultraviolet wavelength of 365 nm, curing time of 5 seconds, and coating thickness of 20μm;
[0076] S2.3: After the coating is cured, the surface of the substrate is cleaned again, and then dried at 80°C for 4 hours. The dried surface of the substrate is electroplated. After the electroplating is completed, the surface of the substrate is baked. The baking parameters are a temperature of 90°C and a drying time of 2 hours. After the baking treatment, the coating is peeled off to protect the surface of the substrate coated with the coating during the electroplating process.
[0077] Example 3
[0078] The preparation method of modified polyurethane acrylate is as follows:
[0079] Dissolving silane coupling agent KH-560 in deionized water to prepare a silane coupling agent solution with a mass fraction of 50%, adding polyurethane acrylate to the silane coupling agent solution, wherein the mass ratio of polyurethane acrylate to silane coupling agent is 1:1, stirring at a speed of 150 r / min, heating to 50° C. while stirring, stirring for 1 hour, then adding 10wt% of vermiculite powder, heating to 65° C., and continuing to stir at a speed of 200 r / min for 1 hour to obtain the modified polyurethane acrylate;
[0080] The preparation method of modified nano hydrated silica is as follows:
[0081] S1.1: dissolving graphene oxide in deionized water and ultrasonicating for 1 h to obtain a graphene oxide solution with a mass fraction of 50%;
[0082] S1.2: Mix hydrated silicon dioxide and aluminum oxide in a mass ratio of 2:1, put them into a ball mill, and grind them at a speed of 400 r / min for 1 h to obtain a mixture A with a particle size of 150 mesh;
[0083] S1.3: Dispersing mixture A in the graphene oxide solution, wherein the mass ratio of mixture A to graphene oxide is 1:1, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture B;
[0084] S1.4: The solid-liquid mixture B was placed in liquid nitrogen and frozen for 15 min. After the freezing, it was dried at -70 °C under vacuum for 4 h to obtain a mixture C.
[0085] S1.5: After adding 2 wt % praseodymium oxide and 1 wt % polyethylene glycol 3000 to mixture C, the mixture was ground in a ball mill at a speed of 500 r / min for 1 h to obtain mixture D;
[0086] S1.6: The mixture D is heated from room temperature to 400°C for calcination at a heating rate of 5°C / min for 3 hours, and the calcined solid is crushed and ground to a particle size of 200 mesh to obtain the modified nano hydrated silica;
[0087] The coating preparation method is as follows:
[0088] According to coating formula 3, modified polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexyl phenyl ketone, trimethylbenzoyl diphenoxyphosphine, modified nano hydrated silica, polyoxyethylene oleate A-110, and silicone defoamer BYK-066N were put into a stirrer for stirring at a stirring rate of 250 r / min for 8 hours to obtain the coating.
[0089] The coating is used as follows:
[0090] S2.1: First, wash the surface of the substrate with deionized water, and then purge it with nitrogen at 70°C for 2 hours at a nitrogen flow rate of 20 m / s to obtain a substrate with a dry surface;
[0091] S2.2: The coating is applied to the substrate surface using screen printing technology, and then UV curing coating is used, with parameters of ultraviolet wavelength of 355 nm, curing time of 10 seconds, and coating thickness of 30 μm;
[0092] S2.3: After the coating is cured, the surface of the substrate is cleaned again, and then dried at 80°C for 4 hours. The dried surface of the substrate is electroplated. After the electroplating is completed, the surface of the substrate is baked. The baking parameters are a temperature of 100°C and a drying time of 1 hour. After the baking treatment, the coating is peeled off to protect the surface of the substrate coated with the coating during the electroplating process.
[0093] Comparative Example 1
[0094] In this comparative example, the polyurethane acrylate was not modified, and the remaining steps were consistent with those in Example 1.
[0095] Comparative Example 2
[0096] In this comparative example, no silane coupling agent is added during the modification of polyurethane acrylate, and the remaining steps are consistent with those of Example 1.
[0097] Comparative Example 3
[0098] In this comparative example, no vermiculite is added during the modification of polyurethane acrylate, and the remaining steps are consistent with those of Example 1.
[0099] Comparative Example 4
[0100] In this comparative example, the nano hydrated silicon dioxide is not modified, and the remaining steps are consistent with those in Example 1.
[0101] Comparative Example 5
[0102] In this comparative example, no alumina is added during the modification process of the nano-hydrated silicon dioxide, and the remaining steps are consistent with those of Example 1.
[0103] Comparative Example 6
[0104] In this comparative example, graphene oxide is not added during the modification process of nano-hydrated silicon dioxide, and the remaining steps are consistent with Example 1.
[0105] Comparative Example 7
[0106] In this comparative example, no rare earth oxide and dispersant are added during the modification process of the nano-hydrated silicon dioxide, and the remaining steps are consistent with those of Example 1.
[0107] The substrate coated with the coating prepared by the present invention was subjected to a wear resistance test, using a JM IV abrasion tester and a rotating friction rubber wheel method, and the wear resistance of the present invention was measured by the average value of the sample mass loss (weight loss method) after 50 grinding revolutions. The load was 10 N, the rotation speed was 80 r / min, the test temperature was 25 ° C, the relative humidity was 50%, and the mass was tested to an accuracy of 0.01 mg. The average value of 3 measurements was taken as the result.
[0108] The scratch resistance of the substrate coated with the coating prepared by the present invention is tested according to the pencil hardness test of GB / T6739-2006. A pencil is fixed on the device and pressed down on the panel surface at a 45° angle under a load of 500g. The hardness decreases from 3H to 3B in sequence; the hardness of the pen tip when a 3mm scratch appears is recorded, and the scratch resistance is scored.
[0109] The water resistance of the embodiments and comparative examples was tested. 2 / 3 of the area of the substrate after coating was placed in distilled water at a temperature of 23°C ± 2°C. After a certain period of time, it was taken out and the surface of the sample was observed to see whether there was blistering, gloss loss, discoloration, etc. The water resistance was ranked from high to low: no gloss loss, no discoloration > gloss loss, discoloration > blistering.
[0110]
[0111] It can be seen from the data of the examples and comparative examples that the modification of polyurethane acrylate and nano-hydrated silica significantly improves the wear resistance, scratch resistance and water washability of the coating.
[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant electroplating protective coating, characterized in that: The coating is composed of the following components by mass percentage: 50-70% of modified polyurethane acrylate, 20-30% of hydroxyethyl methacrylate, 2-5% of hydroxycyclohexyl phenyl ketone, 2-5% of trimethylbenzoyl diphenoxyphosphine, 4-5% of modified nano hydrated silicon dioxide, 1-3% of coloring auxiliary agent, and 1-3% of organic silicon defoaming agent. Wherein, the preparation method of modified polyurethane acrylate is as follows: Dissolving a silane coupling agent in deionized water to prepare a silane coupling agent solution with a mass fraction of 50-60%, adding polyurethane acrylate to the silane coupling agent solution, wherein the mass ratio of polyurethane acrylate to silane coupling agent is 1:1, stirring at a speed of 150 r / min, heating to 50° C. while stirring, stirring for 1 hour, then adding 5-10wt% of vermiculite powder, heating to 65° C., and continuing to stir at a speed of 200 r / min for 1 hour to obtain the modified polyurethane acrylate; The preparation method of modified nano hydrated silica is as follows: S1.1: dissolving graphene oxide in deionized water and ultrasonicating for 1 h to obtain a graphene oxide solution with a mass fraction of 50%; S1.2: Mix hydrated silicon dioxide and aluminum oxide in a mass ratio of 2:1, put them into a ball mill, and grind them at a speed of 400 r / min for 1 h to obtain a mixture A with a particle size of 150 mesh; S1.3: Dispersing mixture A in the graphene oxide solution, wherein the mass ratio of mixture A to graphene oxide is 1:1, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture B; S1.4: freeze the solid-liquid mixture B in liquid nitrogen for 15-20 min. After freezing, dry it at -70--50°C in a vacuum state for 4-6 h to obtain a mixture C. S1.5: After adding 2 wt% of rare earth oxide and 1 wt% of dispersant to mixture C, the mixture was ground in a ball mill at a speed of 500 r / min for 1 h to obtain mixture D; S1.6: The mixture D is heated from room temperature to 400°C for calcination for 3 hours, and the calcined solid is crushed and ground to a particle size of 200 mesh to obtain the modified nano hydrated silica; The coloring auxiliary agent is polyoxyethylene oleate A-110; The silane coupling agent is one of silane coupling agent KH-560 and silane coupling agent KH-792; The coating preparation method is as follows: Modified polyurethane acrylate, hydroxyethyl methacrylate, hydroxycyclohexyl phenyl ketone, trimethylbenzoyl diphenoxyphosphine, modified nano hydrated silica, coloring aid, and silicone defoamer are placed in a blender in proportion and stirred at a stirring rate of 200-300 r / min for 8 hours to obtain the coating.
2. The wear-resistant electroplating protective coating according to claim 1, characterized in that: The organosilicon defoamer is one of BYK-141, BYK-077 and BYK-066N.
3. The wear-resistant electroplating protective coating according to claim 1, characterized in that: The rare earth oxide in S1.5 is one of cerium oxide, lanthanum oxide and praseodymium oxide.
4. The wear-resistant electroplating protective coating according to claim 1, characterized in that: The dispersant in S1.5 is polyethylene glycol, and the number average molecular weight is 2000-4000.
5. The wear-resistant electroplating protective coating according to claim 1, characterized in that: The heating rate from room temperature to 400°C in S1.6 is 5°C / min.
6. A method for using the wear-resistant electroplating protective coating according to any one of claims 1 to 5, characterized in that: The method of use is as follows, S2.1: First, wash the surface of the substrate with deionized water, and then purge it with nitrogen at 70°C for 2-3 hours at a nitrogen flow rate of 20 m / s to obtain a substrate with a dry surface; S2.2: The coating is applied to the substrate surface using screen printing technology, and then UV-cured coating is used, with a coating thickness of 20~30μm; S2.3: The substrate surface after the coating is cured is cleaned again, and dried at 80°C for 4 hours after cleaning. The dried substrate surface is electroplated. After the electroplating is completed, the substrate surface is baked. After the baking treatment, the coating is peeled off to protect the coating-coated part of the substrate surface during the electroplating process.
7. The method for using the wear-resistant electroplating protective coating according to claim 6, characterized in that: The parameters of the UV curing coating in S2.2 are ultraviolet wavelength of 355-365 nm and curing time of 5-10 s.
8. The method for using the wear-resistant electroplating protective coating according to claim 6, characterized in that: The parameters of the baking treatment in S2.3 are a temperature of 100-120° C. and a drying time of 1-2 hours.